The goddess test - Carter, Aimée, 1986- (Harlequin Teen, 2011)
Eden, Michigan, high school student Kate Winters strikes a bargain with Henry, Greek god of the underworld, if he'll cure her dying mother of cancer. The bargain she strikes with him is a grim one, but the full enormity of what she has undertaken--"live forever or die trying"--is not revealed until it's too late to recant.